A spatially and temporally resolved model of the electricity grid – Economic vs environmental dispatch. (15th September 2016) - Razeghi, Ghazal; Brouwer, Jack; Samuelsen, Scott
Graphical abstract: Highlights: A spatially and temporally resolved dispatch model is developed. MCP and average price of electricity are determined for 2050 base case. Economic and environmental dispatch strategies are assessed. Environmental dispatch results in significant NO x reduction and higher prices. A combination of economic and environmental strategies is the preferred method. Abstract: Substantial changes need to occur in the electricity generation sector in order to address greenhouse gas and urban air quality goals. These goals, combined with increasing energy prices, have led to elevated interest in alternative, low to zero carbon and pollutant emission technologies in this sector. The challenge is to assess the impacts of various technologies, policies, and market practices in order to develop a roadmap to meet energy and environmental goals. To this end, a spatially and temporally resolved resource dispatch model is developed that simulates an electricity market while taking into account physical constraints associated with various components of an electricity grid. Multiple technology simulation modules are developed to provide inputs to the model. The model is used to design a market-based grid, and to develop and evaluate different dispatch strategies. To maintain the system cost at acceptable levels and reduce emissions, the results reveal that the best approach is a combination of economic and environmental dispatch strategies. The methodology and the tools developed provide a means to examine various aspects of future scenarios and their impacts on different sectors, and can be used for both decision making and planning.